2011
DOI: 10.1074/jbc.m111.269779
|View full text |Cite
|
Sign up to set email alerts
|

Putative N-Acylphosphatidylethanolamine Synthase from Arabidopsis thaliana Is a Lysoglycerophospholipid Acyltransferase

Abstract: AT1G78690, a gene found in Arabidopsis thaliana, has been reported to encode a N-acyltransferase that transfers an acyl chain from acyl-CoA to the headgroup of phosphatidylethanolamine (PE) to form N-acylphosphatidylethanolamine (N-acyl-PE). Our investigation suggests that At1g78690p is not a PE-dependent N-acyltransferase but is instead a lysoglycerophospholipid O-acyltransferase. We overexpressed AT1G78690 in Escherichia coli, extracted the cellular lipids, and identified the accumulating glycerophospholipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The fatty acid composition of the mitochondrial lipids after deacylation was determined by gas-liquid chromatography (35) using heptadecanoic acid as an internal standard. The mitochondrial phospholipid molecular species were analyzed by liquid chromatography-electrospray ionization quadrupole time-of-flight mass spectrometry (62,63). For radiolabeling of cellular neutral lipids and total phospholipids, cells were grown in SC medium to the late exponential phase (A 600 nm ϳ1).…”
Section: Methodsmentioning
confidence: 99%
“…The fatty acid composition of the mitochondrial lipids after deacylation was determined by gas-liquid chromatography (35) using heptadecanoic acid as an internal standard. The mitochondrial phospholipid molecular species were analyzed by liquid chromatography-electrospray ionization quadrupole time-of-flight mass spectrometry (62,63). For radiolabeling of cellular neutral lipids and total phospholipids, cells were grown in SC medium to the late exponential phase (A 600 nm ϳ1).…”
Section: Methodsmentioning
confidence: 99%
“…1; (Faure et al 2009; Coulon et al 2012)). A more recent study reported that this NAPE synthase enzyme may also have lysoglycerophospholipid O -acyltransferase activity (Bulat and Garrett 2011); however, only NAPE formation was demonstrated for this enzyme in planta (Faure et al 2009), so the physiological significance of this O -acyltransferase activity reported in vitro remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Food intake, body weight, and fat mass during the saturated and monounsaturated NAPEs expected to exert anorexigenic effects (Supplemental Figure 5). In addition to NAPEs, several species with m/z ions consistent with O-acyl-phosphatidylglycerols (acyl-PG) species (34) were also enriched in pNAPE-EcN (Supplemental Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…NAPE concentration was quantified by liquid chromatography-tandem mass spectrometry (LC-MS/MS) after methylamine hydrolysis as we have previously described (33). Because Bulat and Garrett (34) reported that they failed to find evidence for significant synthesis of NAPEs in E. coli expressing At1g76890p, we performed additional experiments to confirm the synthesis of NAPEs category 4: meals >103.3 mg and ≤166.8 mg (mean + 2 SD); category 5: meal events >166.8 mg and ≤230.4 mg (mean + 3 SD). Category X represents meal events >230.4 mg.…”
Section: Methodsmentioning
confidence: 99%